Implementation of the Project for Strengthening the Profile of Pancasila Students in Shaping the Cultural Character of Class V Students at SD Negeri 83 Pekanbaru - Afriani, Wulan; Mustika, Dea (CV. Rayyan Dwi Bharata, 2024)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project in shaping the cultural character of fifth-grade students at SDN 83 Pekanbaru. This research uses a qualitative method with a naturalistic inquiry approach, where data is collected through interviews, observations, and documentation. The research informants consist of the school principal, two teachers, and two students. Data analysis is carried out using the Miles Huberman method, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that project planning involves analyzing goals and objectives, selecting flexible materials and learning resources, and actively involving students in the planning process. The project implementation involves continuous evaluation, active involvement of teachers and students, collaborative learning, the use of creative media and tools, and the application of Pancasila values in daily activities. Project evaluation includes process and outcome assessments, feedback and follow-up, and involvement of parents and the community. In conclusion, the implementation of the Pancasila Student Profile Strengthening Project at SDN 83 Pekanbaru successfully shapes the cultural character of students through a comprehensive and participatory approach. This project not only focuses on academic achievement but also helps students internalize Pancasila values and strengthen their cultural identity. The results of this study are expected to serve as a reference for other schools in implementing similar projects to shape the cultural character of students.